Environment is our mother, mining is our father: contesting gold mining in Turkey - Kök, İrem. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This study dwells into the discursive contestation over the new gold mining investments by utilizing discourse analysis and the actor-based approach. Applying these approaches to the notorious mining conflicts across the world, this thesis advances the argument that discursive battle in the mining conflicts is shaped by the efforts of actors who try to fix their understanding of reality in an effort to garner support for their cause. The process of articulation becomes politically important, as it gives power to opposition groups to act strategically by playing with the discursive field. The Kaz Mountains mining conflict can also be analyzed as a case study of similar discursive contestation. In their animation of the discourses of environmentalism, developmentalism and nationalism, actors try to shape the discursive space by drawing cultural, social and political connections with the local so as to gain support either for pro or anti-mining cause. On the one hand, mining corporations and state articulated powerful discourses of development and environment by drawing a line between the technocratic and the politically-oriented understandings of environment and economic development in order to dismiss the reactions raised by the local opposition and to counter the bad publicity of mining in the eye of people. On the other, local activists successfully carried out the anti-mining cause by articulating new mining investments with ecological, cultural and social destruction and therefore garnered support from local people. All in all, this study seeks to underline the role of actors in shaping the politics of mining conflicts by engaging in imaginative articulation process, and how it empowers the opposition groups to act strategically in their struggle against state and mining corporations.
Keywords: Gold mines and mining -- Turkey.